Mityczny potwór Kampe w „Fasti” Owidiusza - Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The paper discusses Greek and Roman literary sources describing Campe or Kampe (Gk. Κάμπη), a mythical female monster killed by the god Dionysus (Diodorus, Bibl. III 72) or by Zeus (Ps.-Apollodorus, Bibl. I 2,1; Nonnos, D. XVIII 233–264). Campe was a large monster who guarded the Cyclopes and Hundred-Handers prisoned in Tartarus (according to Pseudo-Apollodorus and Nonnos). The same mythical monster seems to be attested in Ovid’s Fasti (III 793–808). The Roman poet presents an unknown version of the Greek myth, describing a wondrous monster (line 799: monstrum mirabile), born of Mother Earth (l. 799: Matre satus Terra). She is portrayed with the upper body of a bull and the tail of a serpent in place of legs (l. 799–800: taurus parte sui serpens posteriore fuit). Ovid does not mention the Greek or Latinized name of this mythical monster but introduces the acrostic CAMPH (= Gk. Κάμπη) in his description (Ov., Fast. III 797–801). Unfortunately, the Ovidian acrostic in question is preserved in the corrupted form CQMPH in most medieval manuscripts. It is suggested that the ancient editor, who prepared the final version of the six books of the Fasti after Ovid’s death (18 AD), failed to notice the Ovidian acrostic and introduced his own improvement in line 798 (quaeque instead of atque or the like).